Professional Port Police: Donald Cassidy’s 1967 Reports on Policing and Security in Canadian Commercial Ports - Madsen, Chris (The Northern Mariner / Le marin du nord, 2024)
In response to a troubling rise in criminal activity in some of Canada’s major commercial seaports during the mid-1960s, the federal Department of Transport engaged a former Royal Canadian Mounted Police/Gendarmerie royale du Canada (RCMP/GRC) member seconded from the Dominion Bureau of Statistics to study the scope of the problem and suggest possible improvements. Two reports were prepared, an internal one for the government harbours board and a public one for the private association representing port managements. A key outcome was creation of the National Harbours Board Police, a new federal police force distinct from the RCMP/GRC. This commentary compares the reports with a table showing the principal recommendations. En réponse à une augmentation inquiétante de l’activité criminelle dans certains des principaux ports maritimes commerciaux du Canada au milieu des années 1960, le ministère fédéral des Transports a engagé un ancien membre de la Royal Canadian Mounted Police/Gendarmerie royale du Canada (RCMP/GRC) détaché du Bureau fédéral des statistiques pour étudier l’ampleur du problème et suggérer des améliorations possibles. Deux rapports ont été préparés, l’un interne pour le conseil gouvernemental des ports et l’autre public pour l’association privée représentant les gestionnaires des ports. L’un des principaux résultats a été la création de la Police du Conseil national des ports, un nouveau corps de police fédéral distinct de la RCMP/GRC. Ce commentaire compare les rapports avec un tableau reprenant les principales recommandations.